Smart sensors simulator / Yogeswari Jayaraman - Yogeswari, Jayaraman (2005)
As part of fulfillment of the requirements for the Bachelor of Computer Science Degree, we are required to do a a thesis on a selected title. My thesis title is Smart Sensor Simulator. This project will be on smart sensors that are based on IEEE 1451.2 standard. Smart sensors are replacing the traditional sensor that were once used. The IEEE 1451 standards specify sets of common communication interfaces to standardize the connectivity of transducers to microprocessor, instrumentation systems, and networks. This is done by specifying different standards the address the various aspect of the development of smart networked transducers. The scope of my thesis wan narrowed down to doing a simulation of the electronic data sheet that is associated with the smart sensors. The electronic data sheet keeps the transducers information. A simulation of how the data sheet keep and retrieve the transducers information to and from the RAM and Flash memory will be done. Hopefully this project will widen my knowledge in smart sensors and serves as a tech bench for those who want to enhance the project.